Isolation and sequence analysis of cDNAs for the major potato tuber protein, patatin. - Mignery, G A (1984)
A cDNA library from membrane-bound poly(A)+ mRNA of developing potato tubers was constructed and two classes of essentially full-length cDNA clones for a precursor to the major tuber glycoprotein, patatin were isolated. Sequence analysis shows that the two classes are approximately 99% homologous and correspond to the two major species of patatin identified previously by NH2-terminal amino acid sequence analysis. Sequence analysis also predicts that patatin is synthesized with a 23 amino acid signal sequence. Northern blot analysis shows that patatin mRNAs are 1550 +/- 50 nucleotides in length and are normally not present in polyribosomal or total RNA from stems or leaves.